1999
DOI: 10.1016/s0896-6273(00)80690-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Face Inversion on Activity in Human Neural Systems for Face and Object Perception

Abstract: The differential effect of stimulus inversion on face and object recognition suggests that inverted faces are processed by mechanisms for the perception of other objects rather than by face perception mechanisms. We investigated the face inversion using functional magnetic resonance imaging (fMRI). The principal effect of face inversion on was an increased response in ventral extrastriate regions that respond preferentially to another class of objects (houses). In contrast, house inversion did not produce a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

47
413
3
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 586 publications
(468 citation statements)
references
References 34 publications
47
413
3
5
Order By: Relevance
“…Recent results extend this notion further and suggest that the processing of inverted faces is more similar to the processing of non-face objects than to that of upright faces (Haxby et al, 1999;Rossion et al, 2000;Rosburg et al, 2010;Kloth et al, 2013), presumably due to the enhanced functional connectivity of the face specific areas with higher-order object sensitive areas (Nguyen et al, 2013). These findings could also explain the increased bold response to inverted as opposed to upright faces, which we observed in the object sensitive LO.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Recent results extend this notion further and suggest that the processing of inverted faces is more similar to the processing of non-face objects than to that of upright faces (Haxby et al, 1999;Rossion et al, 2000;Rosburg et al, 2010;Kloth et al, 2013), presumably due to the enhanced functional connectivity of the face specific areas with higher-order object sensitive areas (Nguyen et al, 2013). These findings could also explain the increased bold response to inverted as opposed to upright faces, which we observed in the object sensitive LO.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, it seems that inversion leads to qualitatively different processing of stimuli belonging to categories of high expertise, such as faces. In line with this specificity, recent behavioral electrophysiological and neuroimaging results suggest that the visual system processes inverted faces more similarly to nonface objects than to upright faces (Haxby et al, 1999;Rossion et al, 2000;Rosburg et al, 2010;Kloth et al, 2013). Therefore, we reasoned that if the face-specificity of P(rep) effects is due to the unique (holistic/configural) processing steps of an upright face then stimulus inversion, a manipulation that interrupts these processing steps, should interfere with the modulatory effects of P(rep) as well.…”
Section: Introductionmentioning
confidence: 87%
“…Early studies of the face-inversion effect in the FFA found little (Haxby et al 1999;Kanwisher et al 1999) or no (Aguirre et al 1999;Leube et al 2003) difference in the response to upright and inverted faces. However, we recently reported a substantially higher FFA response for upright compared with inverted faces (Yovel & Kanwisher 2004).…”
Section: What Is the Nature Of The Face Representations In The Ffa?mentioning
confidence: 97%
“…For example, a schematic drawing consisting of a circle, two dots, and a straight line is recognized as a face, although no individual component of the drawing is part of a real face. Since Bruce and Young (1986) proposed the ''face recognition model'', there have been many studies of face perception using neuroimaging and electrophysiological methods (e.g., Bentin et al 1996;George et al 1996;Haxby et al 1996Haxby et al , 1999Honda et al 2007;Itier and Taylor 2004a;Itier et al 2006;Kanwisher et al 1998;Latinus and Taylor 2006;Miki et al 2007;Rossion and Jacques 2008;Sagiv and Bentin 2001;Shibata et al 2002;Watanabe et al 1999bWatanabe et al , 2002Watanabe et al , 2003Watanabe et al , 2005. In studies of event-related potential (ERP) using averaging electroencephalography (EEG) (e.g., Bentin et al 1996;George et al 1996), static human faces evoked a negative potential in the bilateral occipito-temporal areas peaking at around 170 ms, termed N170, which is considered to be sensitive to faces.…”
Section: Introductionmentioning
confidence: 99%